Effect of duloxetine on neuropathic pain in patients intolerant to continuous administration of pregabalin - Yohei Shimada; Kazuhide Inage; Sumihisa Orita; Masao Koda; Kazuyo Yamauchi; Takeo Furuya; Junichi Nakamura; Miyako Suzuki; Kazuki Fujimoto; Yasuhiro Shiga; Koki Abe; Hirohito Kanamoto; et al. (Spine Surgery and Related Research, 2017)
Purpose: We examined duloxetine's effectiveness in the treatment of neuropathic pain in patients who were intolerant to continuous pregabalin administration. Materials and Methods: The present study is a retrospective study of patients diagnosed with neuropathic pain with neuropathic leg pain as the chief complaint. We analyzed 20 cases in which pregabalin was changed to duloxetine because of adverse effects (16 cases) or treatment failure (4 cases). The incidence of adverse events after duloxetine administration was used as the primary endpoint, with the secondary endpoint being the leg pain level based on a numerical rating scale (NRS). Results: The incidence of adverse events after starting duloxetine was 40%. Average leg pain scores measured on the NRS were 8.4±1.4, 6.4±1.4, and 4.1±2.0 at the time of the patients' first visit, pregabalin discontinuation, and after switching to duloxetine, respectively. A significant difference in NRS scores was found between the first visit and pregabalin discontinuation and also between pregabalin discontinuation and after the switch to duloxetine (p<0.05), indicating that pain decreases over time. Furthermore, NRS scores significantly declined between the patients' first visit and after the switch to duloxetine (p<0.05). The improvement in NRS score was 20±12.8% after pregabalin administration and 23±12.0% after duloxetine administration compared with baseline scores (no significant difference between pregabalin and duloxetine; p>0.05). Conclusion: When patients with neuropathic pain are unable to tolerate pregabalin because of adverse effects, changing the medication to duloxetine may be an option.